2015
DOI: 10.1002/sim.6510
|View full text |Cite
|
Sign up to set email alerts
|

Signal detection in FDA AERS database using Dirichlet process

Abstract: In the recent two decades, data mining methods for signal detection have been developed for drug safety surveillance, using large post-market safety data. Several of these methods assume that the number of reports for each drug-adverse event combination is a Poisson random variable with mean proportional to the unknown reporting rate of the drug-adverse event pair. Here, a Bayesian method based on the Poisson-Dirichlet process (DP) model is proposed for signal detection from large databases, such as the Food a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…The sB method defines the prior distribution of τ ij , where τ ij is the ratio of the mean of the observed frequency distribution and the expected frequency as defined in MGPS, as a Gamma ( a , a ) distribution with identical scale and shape parameters a ∈(0,1). In addition, Hu et al introduce a hierarchical Bayes method that generates the prior for τ ij from a Poisson‐Dirichlet process, providing more flexibility. Norén et al developed a new IC method by using a new shrinkage to the observed‐to‐expected ratio that consists of adding a constant in both numerator and denominator and discuss approaches to use stratification.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The sB method defines the prior distribution of τ ij , where τ ij is the ratio of the mean of the observed frequency distribution and the expected frequency as defined in MGPS, as a Gamma ( a , a ) distribution with identical scale and shape parameters a ∈(0,1). In addition, Hu et al introduce a hierarchical Bayes method that generates the prior for τ ij from a Poisson‐Dirichlet process, providing more flexibility. Norén et al developed a new IC method by using a new shrinkage to the observed‐to‐expected ratio that consists of adding a constant in both numerator and denominator and discuss approaches to use stratification.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…ROR, PRR, IC, and LRT are frequentist methods, while GPS, BCPNN, the new IC method, and sB are Bayesian methods [ 10 ]. Some studies suggest that Bayesian methods, such as multi-item gamma Poisson shrinker (MGPS) and BCPNN, outperform frequentist methods such as PRR [ 2 , 3 , 6 , 7 , 11 ]. Other studies showed that the sB method performed better than BCPNN and PRR [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that Bayesian methods, such as multi-item gamma Poisson shrinker (MGPS) and BCPNN, outperform frequentist methods such as PRR [ 2 , 3 , 6 , 7 , 11 ]. Other studies showed that the sB method performed better than BCPNN and PRR [ 9 , 11 ]. Unlike other methods, the GPS method needs to estimate hyperparameters of the prior distribution using the whole data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from such databases include many different drugs and many different types of AEs across different SOCs. Various methods have been developed for safety signal detection (or detection of drug‐AE pairs) using data from SR; for example, proportional reporting ratios (Evans et al, ), reporting odds ratios (Rothman et al, ), the likelihood ratio tests (Huang et al, , , , ; Nam et al, ; Zhao et al, ), and Bayesian methods (Bate et al, ; DuMouchel, ; DuMouchel and Pregibon, ; Norén et al, ; Hu et al, ).…”
Section: Introductionmentioning
confidence: 99%